1996
DOI: 10.1083/jcb.135.6.1427
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of painted human interphase chromosomes: active and inactive X chromosome territories have similar volumes but differ in shape and surface structure.

Abstract: Abstract. This study provides a three-dimensional (3D) analysis of differences between the 3D morphology of active and inactive human X interphase chromosomes (Xa and Xi territories). Chromosome territories were painted in formaldehyde-fixed, three-dimensionally intact human diploid female amniotic fluid cell nuclei (46, XX) with X-specific whole chromosome composite probes. The colocalization of a 4,6-diamidino-2-phenylindole dihydrochloride-stained Barr body with one of the two painted X territories allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
166
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(193 citation statements)
references
References 55 publications
25
166
2
Order By: Relevance
“…Following DAPI counterstaining with 0.1 mg/ml in PBS for 5 min, the preparations were mounted in Vectashield (Linaris, Wertheim). Optical sectioning was carried out with a Leica TCS 4D confocal microscope as described in Eils et al (1996). To control for bleed through of FITC fluorescence through Cy3-detection filters, we used the 488 nm laser line for FITC excitation in combination with the filters used for Cy3 detection.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Following DAPI counterstaining with 0.1 mg/ml in PBS for 5 min, the preparations were mounted in Vectashield (Linaris, Wertheim). Optical sectioning was carried out with a Leica TCS 4D confocal microscope as described in Eils et al (1996). To control for bleed through of FITC fluorescence through Cy3-detection filters, we used the 488 nm laser line for FITC excitation in combination with the filters used for Cy3 detection.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…The appearance of the Barr body in the nucleus of female cells has led many to speculate that there might be increased chromatin condensation on the Xi (31). However, this idea was questioned by a study that reported equivalent volumes, and hence equivalent levels of overall chromatin condensation, of Xa and Xi (32). That study used X chromosome paints prepared from plasmid libraries and may have lacked the sensitivity to detect decondensed chromatin located at the periphery of the Xa.…”
Section: Discussionmentioning
confidence: 99%
“…4, 6, 7, 11, cells were prepared for in situ hybridization according to our standard protocol (62)(63)(64). For all other experiments, an alternate technique with no air or ethanol dehydration was used (21,50). Cells were fixed before extraction in 4% paraformaldehyde͞PBS for 10 min at room temperature (RT), rinsed in PBS, incubated in 0.1 M HCl for 10 min at RT, extracted in 0.5% triton-X-100͞0.5% saponin in PBS for 10 min at RT and then equilibrated for 20 min in 20% glycerol͞PBS at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed before extraction in 4% paraformaldehyde͞PBS for 10 min at room temperature (RT), rinsed in PBS, incubated in 0.1 M HCl for 10 min at RT, extracted in 0.5% triton-X-100͞0.5% saponin in PBS for 10 min at RT and then equilibrated for 20 min in 20% glycerol͞PBS at RT. Cells were further permeabilized through a freeze-thaw cycle consisting of dipping the coverslip quickly into liquid nitrogen (21). The cells were allowed only to thaw and, if not used immediately, were stored in PBS at 4°C.…”
Section: Methodsmentioning
confidence: 99%